Effect of varying levels of broiler litter on growth performance and nutrient digestibility by West African dwarf lambs (2010)
This study investigated the effect of varying levels of broiler litter wastes on growth performance and nutrient digestibility of WAD lambs. Sixteen rams were allotted into 4 groups while 4 experimental diets were formulated using 0, 25, 50 and 75% levels of broiler litter in their diets respectively. The parameters studied included dry matter (DM) intake and nutrient digestibility of the lambs. Results obtained showed that DM intake increased with increasing values of BL in the diet. Similarly, metabolic DMI values obtained were inconsistent with the increasing levels of BL in the diet. All ram lambs gained weight but the rate of gain across the treatments were significantly different (P<0.05) between diets 1 to 3 and 4. Furthermore, it was observed that with the increasing levels of BL in the diet, mean live weight of the animals decreased. Consequently, from the performance of the experimental animals, it can be concluded that broiler litter can be applied in any ruminant production venture as a supplement without any adverse effect at 50% inclusion level.